Styles of mesoscale brittle deformations associated with the Miocene folding of the Taishu Group, Tsushima, between the Japan Sea and East China Sea backarc basins. (8th March 2021) - Yamaji, Atsushi; Yanagisawa, Tatsuhiko; Sato, Katsushi
Abstract: The Taishu Group is a folded, Eocene–Lower Miocene, thick sedimentary package exposed widely on Tsushima Island between the Japan Sea and East China Sea. This location makes the strata important to understand tectonics and paleo‐environments in the Far East, but the timing of the folding is controversial. We studied the styles of brittle deformations of the strata. It was found that flextural‐slip folds were dominant. Mesoscale faults were classified into two groups: NE–SW trending reverse faults and NW–SE trending strike‐slip faults. Members of both the groups showed movements largely perpendicular to the fold axes. The latter group consisted of sinistral and dextral faults. Accordingly, we interpreted that they were transfer faults activated during the folding. Consequently, mesoscale faults and flexural‐slip faults evidence the map‐scale plane strain of the Taishu Group in the plane perpendicular to the NE‐trending fold axes. There were few transpressional deformations in the group. This is inconsistent with the transpression hypothesis for explaining the simultaneous folding and Japan Sea opening. Another hypothesis in which the folds in Tsushima are regarded as an onshore part of the Taiwan‐Shinji fold belt is inconsistent with the timing of folding suggested by mining geologists to be consistent with and contemporaneous with this deformation. On the other hand, we found that dolerite dikes and sills were involved in the folding. Therefore, we conclude that the folding began during the late Early Miocene time and climaxed during the ore mineralization at around 15 Ma. We suggest that the folding in Tsushima was the easternmost manifestation of the compressional regime around the Yellow Sea and East China Sea in the Early to early Middle Miocene, and that the compression was brought about by the arrival of the Philippine Sea plate to initiate buoyant subduction under Kyushu.